Cholesterol Side-Chain Cleavage Gene Expression in Theca Cells: Augmented Transcriptional Regulation and mRNA Stability in Polycystic Ovary Syndrome - Wickenheisser, Jessica K.; Biegler, Jessica M.; Nelson-DeGrave, Velen L.; Legro, Richard S.; Strauss, III, Jerome F.; McAllister, Jan M. (PLOS ONE, 2012)
Hyperandrogenism is characteristic of women with polycystic ovary syndrome (PCOS). Ovarian theca cells isolated from PCOS follicles and maintained in long-term culture produce elevated levels of progestins and androgens compared to normal theca cells. Augmented steroid production in PCOS theca cells is associated with changes in the expression of genes for several steroidogenic enzymes, including CYP11A1, which encodes cytochrome P450 cholesterol side-chain cleavage. Here, we further examined CYP11A1 gene expression, at both the transcriptional and post-transcriptional level in normal and PCOS theca cells propagated in long-term culture utilizing quantitative RT-PCR, functional promoter analyses, and mRNA degradation studies. The minimal element(s) that conferred increased basal and cAMP-dependent CYP11A1 promoter function were determined. CYP11A1 mRNA half-life in normal and PCOS theca cells was compared. Results of these cumulative studies showed that basal and forskolin stimulated steady state CYP11A1 mRNA abundance and CYP11A1 promoter activity were increased in PCOS theca cells. Deletion analysis of the CYP11A1 promoter demonstrated that augmented promoter function in PCOS theca cells results from increased basal regulation conferred by a minimal sequence between −160 and −90 bp of the transcriptional start site. The transcription factor, nuclear factor 1C2, was observed to regulate basal activity of this minimal CYP11A1 element. Examination of mRNA stability in normal and PCOS theca cells demonstrated that CYP11A1 mRNA half-life increased >2-fold, from approximately 9.22+/−1.62 h in normal cells, to 22.38+/−0.92 h in PCOS cells. Forskolin treatment did not prolong CYP11A1 mRNA stability in either normal or PCOS theca cells. The 5′-UTR of CYP11A1 mRNA confers increased basal mRNA stability in PCOS cells. In conclusion, these studies show that elevated steady state CYP11A1 mRNA abundance in PCOS cells results from increased transactivation of the CYP11A1 promoter and increased CYP11A1 mRNA stability.